Septic arthritis of the hip joint by Salmonella typhi; A Case Report and Review of Literature - Tariq, Hira; Izhar, Mateen; Aslam Khichi, Muhammad; Ahmad, Nazia; Tariq, Anam; Rizwan Rasheed, Muhammad; Hammad, Maryam (Pakistan Journal of Medical & Health Sciences, 2022)
We report a case of septic arthritis of hip joint in a 10-year-old boy with enteric fever. The clinical diagnosis was confirmed by Salmonella typhi isolation from joint aspirate obtained by FNAC. Treatment with intravascular Imipenem injections was successful